2014
DOI: 10.1007/s11096-014-9955-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria in adults with sickle-cell disease: the role of hydroxycarbamide(hydroxyurea) as a protective agent

Abstract: SCD is associated with important renal abnormalities. Hydroxycarbamide seems to protect kidney function in SCD by decreasing proteinuria but not microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…We did not find significant differences in creatinine, urine osmolality, cystatin C, or estimated GFR, suggesting that renal pathology may have been too far advanced or that 1 year was not sufficient to reverse these kidney parameters. However, similar to other studies, hydroxyurea significantly decreased albuminuria in our patients 45,46,49,50 . In fact, of 3 patients with macroalbuminuria at baseline, protein levels decreased to the microalbuminuria range in 1 patient and no albuminuria range in 1 patient.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not find significant differences in creatinine, urine osmolality, cystatin C, or estimated GFR, suggesting that renal pathology may have been too far advanced or that 1 year was not sufficient to reverse these kidney parameters. However, similar to other studies, hydroxyurea significantly decreased albuminuria in our patients 45,46,49,50 . In fact, of 3 patients with macroalbuminuria at baseline, protein levels decreased to the microalbuminuria range in 1 patient and no albuminuria range in 1 patient.…”
Section: Discussionsupporting
confidence: 91%
“…Hydroxyurea has been reported to decrease cortical iron kidney deposits in a patient with SCD 44 . Further, hydroxyurea has been shown to prospectively decrease proteinuria in adults and children with SCD 45,46 and was associated with a lower prevalence of albuminuria in adults with SCD 47 . Although hydroxyurea dosed at MTD significantly decreased GFR in children with SCD, there was no significant change in cystatin C levels, and a randomized, placebo‐controlled trial of fixed dose hydroxyurea (20 mg/kg/day) in infants did not show improvement in GFR between those receiving hydroxyurea versus placebo 11 ; however, infants receiving hydroxyurea had significantly higher urine osmolality and decreased kidney enlargement, implying some benefit to the kidneys 48 .…”
Section: Discussionmentioning
confidence: 96%
“…Approximately 12% of patients with SCD have chronic renal failure, which is associated with significant morbidity and mortality 9. Use of hydroxyurea may be beneficial to prevent the progression of sickle cell nephropathy10 by decreasing the degree of proteinuria,11 which is perhaps correlated with increased Haemoglobin F 12. Hydroxyurea reduces the production of RBCs with predominant Haemoglobin S by inhibiting ribonucleotide reductase, with subsequent compensatory increase in RBC with Haemoglobin F formation by activating the γ- gene 4.…”
Section: Discussionmentioning
confidence: 99%
“…The use of hydroxyurea (HU) has been suggested to reduce proteinuria and hyperfiltration as suggested in one prospective study consisting of 26 patients with SCD. However, no effect on microalbuminuria was found [77,149]. A cross-sectional study of 149 adult patients showed that those using hydroxyurea were less likely to exhibit albuminuria (defined as urinary urinary-creatinine ratios ≥30 mg/g) [149].…”
Section: Treatment Of Proteinuriamentioning
confidence: 99%
“…However, no effect on microalbuminuria was found [77,149]. A cross-sectional study of 149 adult patients showed that those using hydroxyurea were less likely to exhibit albuminuria (defined as urinary urinary-creatinine ratios ≥30 mg/g) [149]. A multi-center trial in infants (mean age 13.8 months) demonstrated that treatment with hydroxyurea for 24 months did not influence the GFR.…”
Section: Treatment Of Proteinuriamentioning
confidence: 99%